Anesthetic efficacy of articaine and lidocaine in endodontic treatment of mandibular molars with symptomatic irreversible pulpitis - Quynh, Pham Le Xuan; Khanh, Hong Quoc; Bay, Phan Thi; Khue, Truong Nhut (Tạp chí Nghiên cứu Y học, 2026)
Achieving adequate anesthesia in mandibular molars with symptomatic irreversible pulpitis remains challenging. This study compared the anesthetic efficacy of two common clinical regimens, 4% articaine via buccal infiltration and 2% lidocaine via inferior alveolar nerve block. A controlled clinical study was conducted on 60 mandibular molars with symptomatic and electric pulp test (EPT) responses were recorded. Pre-injection pain was comparable between groups (p = 0.528). Post-injection pain was significantly lower in the articaine group (30.8 ± 16.4 vs 38.4 ± 24.8, p = 0.040). The need for supplemental anesthesia was lower in the articaine group than in the lidocaine group (23.3% vs 46.7%, p = 0.046). Pain during instrumentation was also lower with articaine (p = 0.044), whereas no difference reported during access or obturation. The time to achieve a negative EPT response was shorter with articaine (8.6 ± 2.3 vs 10.1 ± 3.4 minutes, p = 0.048). The overall success rate was significantly higher in the articaine group (76.7% vs 53.3%, p = 0.048). To conclude, the articaine buccal infiltration regimen demonstrated superior anesthetic efficacy compared with the lidocaine via inferior alveolar nerve block regimen, particularly in reducing post-injection pain, shortening onset time, and decreasing the need for supplemental anesthesia.